Diagnosis automática con 5G para entornos de emergencia - Trujillo, José Antonio; De la Bandera Cascales, Isabel; Barco-Moreno, Raquel (My University, 2023)
Emergency communications are a fundamental aspect for any community, becoming more necessary year after year. This fact, together with the continuous advance of mobile network technologies, enables increasingly more reliable and faster communications in critical situations. The aim of this work is to provide a diagnostic system to detect the specific failures that occur in a mobile network in an emergency situation. In the same way, the proposed methodology is also capable of providing the most suitable solution to mitigate the effects that the disaster or emergency has caused in the network.
Keywords: Telecomunicaciones; Sistemas de comunicaciones móviles; Self-Organizing Networks; Mobile Communications; Emergency situations; Machine learning